Calculation of Unit Cost School Information System Development using ABC (Activity Based Costing) Method - Hakim, Muhammad Fahson; Nuha, Ahmad Sirojun; Lathifah, Widya Aini; Yaqin, M. Ainul (Proceeding International Conference on Science and Engineering, 2020)
In developing an information system the school must determine a strategy in its development. Look for managers who are reliable in making decisions that are oriented to reliable development. One of the proper management concepts is cost accuracy. Accuracy of charging costs on cost objects is very important for users of cost information. Beside the accuracy, it is also needed to find out the cost per unit needed in the information system. This is intended to have a price benchmark for the development of information systems in the future. In this study the unit cost calculation uses the ABC (Activity Based Costing) method which emphasizes the cost calculation for the activities involved. The allocation of costs is based on salary data from trusted institutions, namely the Pedoman Standard Minimal 2019 by INKINDO. The results of this study get a total cost value of 18.407.082,00while the cost of each complexity is 5,301.00 with the standard cost of procurement of goods and services issued by the government and several survey institutions.